Fracture and fatigue behavior of Bambusa Vulgaris-Schrad Bamboo. Issue 1 (1st January 2021) - Onche, Emmanuel O.; Oyewole, Oluwaseun K.; Obayemi, John D.; Ekwe, Nneka B.; Rahbar, Nima; Soboyejo, Winston O.
Abstract: This paper presents the results of an experimental study of the fatigue and fracture behavior of Bambusa Vulgaris-Schrad bamboo. Mechanisms of crack initiation and growth are elucidated under monotonic and cyclic compressive failure or flexural loading. The microscopic studies of fatigue and fracture explore the effects of fiber/crack/ply orientation on crack growth and toughening mechanisms in single-edge notched and double -edge notched fracture mechanics bend specimens, which are studied in the "crack-arrestor" and "crack-divider" orientations. The compressive fatigue behavior of Bambusa Vulgaris-Schrad bamboo is also investigated in smooth un-notched specimens. The resulting stress-life behavior is shown to occur in a regime in which the maximum stresses exceed the critical conditions for the onset of progressive fiber buckling and shear band formation. This results ultimately in the nucleation and propagation of interlaminar cracks and shear cracks across the Bambusa Vulgaris-Schrad structures. The implications of the results are discussed for the design of robust bamboo structures.